Laser-activated nanoparticles for ultrasound/photoacoustic imaging-guided prostate cancer treatment - Xiao, Linkang; Wu, Yunfang; Dai, Junyong; Zhang, Weili; Cao, Yang (Frontiers in Bioengineering and Biotechnology, 2023)
Prostate cancer (PCa) is the most common malignant tumor in men. Prostate-specific membrane antigen (PSMA), which is overexpressed on the surface of PCa cells, may serve as a potential therapeutic target. Recently, image-guided and targeted therapy for prostate cancers has attracted much attention by using PSMA targeting nanoparticle. In this study, we produced PSMA-targeted light-responsive nanosystems. These nanosystems of liquid perfluorocarbon cores and polymer shells were loaded with the photosensitizer IR780 and therapeutic drugs paclitaxel. The liquid perfluorocarbon (PFP) in nanoparticles can perform ultrasound-enhanced imaging by liquid-gas transition and promote the deliver and release of paclitaxel. IR780 can perform photothermal therapy (PTT) guided by photoacoustic (PA) imaging. Combination treatment with PTT and chemotherapy exhibited excellent inhibition of cell proliferation in vitro and a significant therapeutic effect in vivo. In conclusion, we successfully formulated PSMA-targeted nanosystems with precision targeting and ultrasound/PA dual-modality imaging for anti-tumor effects.